Embedded students? Can libraries benefit from students having work placements in the library in planning library instruction? - Johannessen, Hilde Terese Drivenes (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2019)
This article discusses how students can be more integrated in developing library instruction and what advantages that can provide for librarians planning their teaching. The students seem to have a different starting point as to how important the librarians’ knowledge of the subject at hand is and whether or not library instruction should be an integrated part of the course.